Program evaluation of English language learning for EYL curriculum development in Indonesia: teachers - Metty Agustine Primary; Emi Emilia; Didi Sukyadi (Journal on English as a Foreign Language, 2023)
Program evaluation (henceforth PE) is a phase of curriculum development in the ELT context and is precious for improving curriculum reform. However, more research needs to be undertaken to investigate PE as a part of the English curriculum development for young learners